Outcome of Stapled Hemorrhoidectomy versus Traditional Hemorrhoidectomy in Patients with Advance Hemorrhoids (Medical Forum Monthly, 2024)
Objective: To evaluate the outcome of stapled hemorrhoidectomy versus traditional hemorrhoidectomy in patients presenting with advance hemorrhoids.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Department of Surgery, University of Lahore Teaching Hospital Lahore from January 2018 to December 2018.Materials and Methods: A total of 150 patients of both genders with ages 20 to 70 years who presented with advance hemorrhoids were included. Patient’s demographical details including age, sex and residence were recorded. Patients were categorized in two groups; Group I consist of 75 patients and received stapled hemorrhoidectomy and Group II contains 75 patients and received traditional hemorrhoidectomy. Post-operative outcomes of both groups were recorded and findings compared between both groups. Follow-up was taken at 6 and 12 months after surgery to examine the recurrence rate.Results: There were 45 (60%) male patients and 30 (40%) females in Group I and 48 (64%) patients were males and 27 (36%) were females in Group II. In Group I recurrence was found in 8 (10.66%) patients and in Group II 10 (13.33%) patients developed recurrence. Time duration of surgery was high in Group II patients 40.4±6.9 min. as compared to Group I 29+5.23 min. In Group I mean pain score was 6.23+2.24 and in Group II it was 7.2+1.45 according to the VAS. In group II 7 (9.33%) patients had postoperative pain and in Group I, 3 (4%) patients had postoperative pain. Post operative bleeding found in 8 (10.67%) patients in Group II and 2 (2.67%) in Group I.Conclusion: Stapled hemorrhoidectomy is a safer and effectivetechnique with low rate complications as compared to traditional hemorrhoidectomy.